ANALYSIS OF DETERMINANTS FOR OPEN INNOVATION IMPLEMENTATION IN REGIONAL INNOVATION SYSTEMS (INMR - Innovation & Management Review, 2017)
This study deals with the challenge of implementing an Open Innovation strategy in Regional Innovation Systems. In this context, our research question is: can a Regional Innovation Systems be a favorable environment for Open Innovation implementation? To address this question, the main objective of this paperwas to identify and analyze the determinant factors for a successful implementation of Open Innovation in Regional Innovation Systems. The factors were empirically tested through qualitative research involving seven of the key actors in a Regional Innovation Systems in the Paraná state, in southern Brazil. The results suggest that some of the determinants factors and conditions for Open Innovation implementation are: proximity and close relationship with Higher Education Institutions; existence of a governance system to intermediate relationships with knowledge actors outside the regional system; mechanisms of relationship network and knowledge absorptive capacity by the firms constituting the Regional Innovation Systems; and provision of public support (e.g., incentives, funding, infrastructure). Since these determinants are present in the Regional Innovation Systems in question, we conclude that the Regional Innovation Systems offers a favorable environment to Open Innovation implementation. Additionally, we highlight a number of contributions and implications for academics, practitioners and those interested in Regional Innovation Systems governance.rac